Seedling response to water stress in valley oak (Quercus lobata) is shaped by different gene networks across populations - Mead, Alayna; Peñaloza Ramirez, Juan; Bartlett, Megan; Wright, Jessica; Sack, Lawren; Sork, Victoria (Dryad, 2019)
Drought is a major stress for plants, creating a strong selection pressure
for traits that enable plant growth and survival in dry environments. Many
drought responses are conserved species-wide responses while others vary
among populations distributed across heterogeneous environments. We tested
how six populations of the widely-distributed California valley oak
(Quercus lobata) sampled from contrasting climates would differ in their
response to soil drying relative to well-watered controls in a common
environment by measuring ecophysiological traits in 93 individuals and
gene expression (RNA-seq) in 42 individuals. Populations did not differ in
their adjustment of turgor loss point during soil-drying, suggesting a
generalized species-wide response. Differential expression analysis
identified 689 genes with a common response to treatment across
populations, and 470 genes with population-specific responses. Weighted
gene co-expression network analysis (WGCNA) identified groups of genes
with similar expression patterns that may be regulated together (gene
modules). Several gene modules responded differently to water stress among
populations, suggesting regional differences in gene network regulation.
Populations from sites with a high mean annual temperature responded to
the imposed water stress with significantly greater changes in gene module
expression, indicating that these populations may be locally adapted to
respond to drought. We propose that this variation among valley oak
populations provides a mechanism for differential tolerance to the
increasingly frequent and severe droughts in California.
This dataset is for a study in which Quercus lobata (valley oak) seedlings
from six sites were grown in a greenhouse and subjected to a water stress
or control treatment for 10 or 20 days. Gene expression data for a subset
of seedlings was obtained through RNAseq on leaf tissue for control and
treated seedlings at 10 days.   Data processing for fastq files:
Converted raw reads from qseq to fastq files. Reads failing the Illumina
quality filter were removed and reads were demultiplexed. Scripts are
available at github.com/alaynamead/RNAseq_scripts   Data
processing for gene counts file: Converted raw reads from qseq to fastq
files (github.com/alaynamead/RNAseq_scripts) The fastq files were
demultiplexed (github.com/alaynamead/RNAseq_scripts) Reads were trimmed
for quality (<27) and adapters, and short reads (<20 bp)
were removed (Cutadapt version 1.12) Aligned to Q. lobata transcriptome
using end-to-end alignment with default 'sensitive' parameters
(Bowtie2) Removed reads with mapping quality (MAPQ) score <20
(Samtools version 0.1.19) Removed potential exclusion amplification
(ExAmp) duplicates (github.com/afontenot/mark-duplicates)
File descriptions   fastq files: 42 gzipped fastq files, one for
each sequenced individual and named with individual ID. Files include the
demultiplexed raw reads for each seedling. Reads failing the Illumina
quality filter were removed but no other processing was done. Read names
have 6 fields, separated by a colon ":" – instrument name, run
name, lane number, tile number, x coordinate, y coordinate.
experiment_design.csv: Includes collection site, treatment, maternal
family, sequencing lane, and library preparation batch for each individual
sequenced.   gene_counts.csv: Raw transcript counts for each gene
(rows) and each seedling (columns).   seedling_trait_data.csv:
Data for each seedling with the following information. Includes some
missing values as "NA" when a measurement was not collected for
an individual. Site: location acorn was collected from Tree: individual
seedling ID mom: maternal family ID Treatment: control1 and drought1
(control and water stress treatment after 10 days) or control2 and
drought2 (control and water stress treatment after 20 days). Family_Wt:
acorn weight of family (g) Days_to_germ: average days to germination for
seedlings from the same maternal family Diameter: seedling basal diameter
(cm) Height: seedling height (cm) larg_leaf_length, larg_leaf_width,
larg_leaf_thick: length, width, and thickness of the largest leaf (mm)
Ave_Thick (two measurements and average): average thickness of two leaves
(mm) Osmometer_mpa (two measurements): osmometer measurement used for
turgor loss point calculation TLP_mpa (two measurements and average): leaf
water potential at turgor loss point (MPa) Area (two measurements and
average): leaf area (mm) dry_mass (two measurements and average): leaf dry
mass (g) soil_mass (two measurements and average): soil mass (g) soil
water potential (two measurements and average): soil water potential (MPa)
leaf_water_potential (two measurements and average): leaf water potential
(MPa) Latitude, Longitude, Elevation_m: location of tree from which the
acorn was collected (elevation in meters) WP_avg_leaf_soil_diff: average
leaf water potential – average soil water potential (MPa)
Keywords: turgor loss point; Water stress